An Analysis of Person and Spatial Deixis Song Lyric of Adele’s Songs - Ula Nisa El Fauziah; Puja Latifah Sari (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
This research aims to determine the person and spatial deixis used in Adele's song lyrics. Descriptive qualitative techniques were used to collect statistics. They categorize them into deixis forms based on their standards, and their findings are that types of deixis, such as individual deixis and spatial deixis, use song lyrics by using Adele. From the study results, it can be concluded that character deixis and spatial deixis of placement and dialogue are present in all song lyrics, personal deixis is most commonly found in 299 phrases, namely the words “I, you, me, and you dominate all songs. Spatial deixis is located in a 16-phrase. This can be seen from the character deixis from the final evaluation results and spatial deixis, which may be found in many of the six-song lyrics. It is the writer's great hope that this research can assist readers in studying the types of persons and spatial deixis.